The rejection that changed my life 25 powerful women on being let down, turning it around, and burning it up at work - Jessica Bacal (New York Plume, Penguin Random House LLC, 2021)
"The perfect gift and conversation starter for women who talk about dealing with failure and accepting not being perfect, this book features fascinating interviews with twenty-five women, including Keri Smith, Angela Duckworth, and Roz Chast, about triumphing over career setbacks and challenges. Jessica Bacal, the author of Mistakes I Made at Work, is a well-respected career-development professional at Smith College"-- Provided by publisher.
Keywords: Rejection (Psychology)